Fertilization integrated with microbial inoculants improves bell pepper production. Issue 4 (4th July 2022) - Tanwar, Anju; Singh, Ajay; Aggarwal, Ashok; Badda, Neetu; Kaur, Rubdeep; Kumar, Ravindra
ABSTRACT: Increased use of fertilizers under intensive agriculture has the possibility of environmental contamination. The use of microbial inoculants may be effective in sustaining crop productivity, soil health, and supplementing chemical fertilizers. The investigation evaluated responses of arbuscular mycorrhizal (AM) fungi, Glomus mosseae (G) and Acaulospora laevis (A) and the bacterium Pseudomonas fluorescens (Pf) on bell pepper ( Capsicum annuum L.) when provided superphosphate at F1 = 60 kg ha −1 (0.45 g/pot), F2 = 120 kg ha −1 (0.90 g/pot), or F3 = 240 kg ha −1 (1.80 g/pot). Plant growth, nutrient content, and yield 120 days after transplanting (DAT) were determined. Plants responded best to F1 followed by F2, while F3 produced inhibitory effects. The highest AM colonization and spore numbers were with G + A+ Pf, resulting in an increase in chlorophyll content, root phosphatase activity, shoot fresh weight, early fruit formation, number of fruit/plant, fruit size, weight, and early ripening. Inoculation with G. mosseae alone increased leaf area, photosynthesis, plant height, root freshness and dry weight. The G+ Pf commonly produced highest shoot fresh weight and fruit nutrient content. The effectiveness of these inoculants on bell pepper growth and yield was highest; 60 and 120 kg ha −1 P -fertilizer level when amended with G + A+ Pf. Use of AM or micro-inoculants may reduce fertilizer input and enhance nutrient utilization efficiency, which positively affected qualitative characteristics, nutrient uptake, and resistance to suboptimal conditions, but has few or little effect on quantitative characteristics. More work is needed to determine optimum rates of the materials tested to produce marketable size fruit.